Case report: Paraganglioma masquerading as angiosarcoma: diagnostic‐dilemma in vascular tumors - Rajoo, Ahilan Raj; Kannairan, Saravanan; Habeebullah Khan, Hisham Arshad; Md Idris, Mohamad Azim; Tan, Geok Chin; Chandra Sakaran, Kishen Raj; Safri, Lenny Suryani (Frontiers in Oncology, 2024)
Paragangliomas originating from blood vessels are exceptionally rare, presenting diagnostic challenges due to their histological resemblance to other vascular neoplasms. We present a case study of a 60-year-old woman with underlying hypertension and dyslipidemia with obesity, initially diagnosed with angiosarcoma based on imaging and histological characteristics viewed via CT-guided biopsy. Intraoperative exploration revealed a lobulated tumor located between the inferior vena cava (IVC) and aorta measuring 7 cm × 8 cm, during which the patient developed transient hemodynamic instabilities. Histopathological examination and immunohistochemical staining using neuroendocrine markers (chromogranin, synaptophysin, S-100 protein, and CD-56) later confirmed the tumor as a retroperitoneal paraganglioma. Retroperitoneal paraganglioma was initially misdiagnosed as angiosarcoma due to the overlapping imaging characteristics between the two tumors. This highlights the importance of raising suspicion on the possibility of retroperitoneal paraganglioma when imaging examination indicates angiosarcoma and to incorporate histopathological examination and immunohistochemistry in the diagnosis to avoid misdiagnosis.